Shakespeare's early comedies: studies in The comedy of errors, The taming of the shrew and The two gentlemen of Verona - Bryant, Peter (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1970)
This dissertation offers fairly full readings of three early Shakespearean comedies. Because these works are still partly misunderstood, it has seemed reasonable to lay the critical emphasis on explication, though a certain amount of judging has been inevitable. The aim has been to induce recognition of aspects of these plays to which much modern criticism has seemed opaque.
Keywords: Shakespeare, William, 1564-1616 -- Comedy of Errors; Shakespeare, William, 1564-1616 -- Comedies Shakespeare, William, 1564-1616 -- Two gentlemen of Verona; |Shakespeare, William, 1564-1616 -- Taming of the shrew